Work environment of automated and non-automated rice mills in Amapara district, Sri Lanka - Chandrathilaka, K. R. M.; De Alwis Seneviratne, S. R.; Lankatilake, K. N.; Samaranayake, D. B. D. L.; Karunarathna, A. K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Paddy cultivation is a major occupation in informal sector in Sri Lanka. In 2014, contribution of the agricultural activities to the country’s annual GDP was 9.9% of which, contribution by paddy was 11.3%. The objective of the current study was to describe the work environment in rice mills with respect to dust, humidity and thermal condition, ventilation and illumination. Methods: A cross sectional study in 107 randomly selected rice mills was carried out in Ampara district in Sri Lanka. Standardized measurements were carried out to assess internal work environment of the mills. Results: Milling activities showed a seasonal variation. The majority of the mills (95.3%) manufactured raw rice only. Other than the basic characteristics, both automated (AMs) and non-automated mills (NAMs) showed common features. All rice mills exceeded the threshold limit values for total (520.04 mg/m3, SD=191.86 mg/m3) and respirable dust (48.14 mg/m3, SD=9.4 mg/m3). Mean daytime indoor relative humidity in the majority of the mills (n=102, 95.3%) was within the accepted upper limit. In most of the mills, ventilation (n=84, 78.5%) and illumination in polishing/packing area (n=60, 56.1%) was satisfactory while in dehusking/paddy inlet area (n=96, 89.7%), illumination was below the limits. Conclusions: Work environment in both the AMs and NAMs in Ampara district presented with poor work standards compared to the required guidelines.